2014
DOI: 10.4103/2230-8598.133114
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-demographic and treatment seeking profile of children below 15 years attending the anti-rabies clinic

Abstract: Background: Rabies being 100% fatal disease, every individual is vulnerable to animal bite irrespective of age, sex and socio-economic status. Children are at greater risk. Though most of the bites are by pet animal and provoked, they are more severe, usually on proximal part of the body including face, neck and scalp and thus lifethreatening. Materials and Methods: A cross-sectional hospital based study in the anti-rabies vaccination (ARV) clinic from November to April 2013. Every new child below 15 years att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Nearly 32.49% of children were less than 5 years which is a serious issue. 2 A study done by Behera et al and Mohanty et al showed prevalence of animal bite in children from 0 to 14 years to be more than 33%. 6,7 Dog bite was the most common similar to those found by Bedi et al and Behera et al In our study although most common injury was abrasion, around 16.42% of the children suffered lacerated wounds, thus increasing the severity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nearly 32.49% of children were less than 5 years which is a serious issue. 2 A study done by Behera et al and Mohanty et al showed prevalence of animal bite in children from 0 to 14 years to be more than 33%. 6,7 Dog bite was the most common similar to those found by Bedi et al and Behera et al In our study although most common injury was abrasion, around 16.42% of the children suffered lacerated wounds, thus increasing the severity.…”
Section: Discussionmentioning
confidence: 96%
“…Still today when treatment options in the form of vaccine, immunoglobulin are available, people as well as health care professional preferably in the peripheral hospitals have not realized its importance and thus treatment received is often not complete and satisfactory. 2 Vast majority of the estimated 55,000 deaths caused by rabies each year occur in rural area of Africa and Asia. In India alone, 20,000 deaths are estimated to occur annually.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from different part of country has supported this consideration by showing that most common sites for animal bite were upper and lower extremities. 17,[19][20][21] Our study also tried to assess awareness about disease caused by dog bite. In present study, 71.9% subjects had heard word 'Rabies'.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of animal bites was determined as 2.82 cases per 1000 people in Iran and 1.55 per 1000 residents in Canada . Children below 15 years of age were at greater risk for animal bites, with a reported incidence rate of 32.98% in India . Epidemiological data indicated that 19 million humans were bitten by animals in Southeast Asia every year .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies in India, Sri Lanka, and Nigeria indicated that domestic animals were responsible for most exposures. Some studies reported that animal bites were mainly provoked, while other studies indicated that most animal bites were unprovoked …”
Section: Introductionmentioning
confidence: 99%